THE EFFECTIVENESS OF DICTOGLOSS METHOD ON LISTENING SKILL OF NARRATIVE TEXT AT TENTH GRADE STUDENTS OF MA AL IMAN ADIWERNA TEGAL - Tuty Alawiyah; Farouk Imam Arrasyid (IAIN Syekh Nurjati Cirebon, 2016)
Abstract:Many problems based on condition of learning listening at tenth grade students of MA Al-Iman Adiwerna Tegal, students difficult to understand the topic or, content of spoken. This research method is quantitative, that used quasi experiment design. The population was at the tenth grade students of MA Al-Iman Adiwerna Tegal with a total number of 90 students and 61 students were taken as sample. The data were collected by using multiple choice listening test (pre and post-test). The finding show the t-test result it can be seen that tcount is 2.289 and ttable = 1.671. So, the researcher made the conclusions of the hypothesis that tcount is higher than ttable namely 2.571>1.684 an from formula of t-test shown that to > tt namely 0,026 < 0,05, In other word, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. It means that there is positive and significant effect of using dictogloss method on listening skill of narrative text. It means that there is positive and significant effect of using dictogloss method on listening skill of narrative text at Tenth Grade Students of Ma Al Iman Adiwerna Tegal. Keyword: Dictogloss method, Listening Skill, Narrative Text.